Embryonic development and larval tolerance to salinity of Scylla oceanica (Dana,1852) - Pura, Zandro Villaroya (University of the Philippines in the Visayas, 1997)
The embryonic development of Scylla oceanica were documented by measuring the egg diameter, heartbeat/min : and the incubation period. Larval tolerance to salinity was also conducted at 15, 20, 25, 30, 35 and 40 ppt. For the control, available seawater in the hatchery was used. Pond-reared female crabs with matured gonad were bought from local market. A 295g broodstock spawned naturally after 8 days in the laboratory tank at 28.81 + 0.92 C and 29.0 + 0.03 ppt. However, a 595 g crab spawned after 19 days at 29.86 + 0.75 C and 29.42 + 1.43 ppt. The eggs immediately attached to the pleopod of the abdominal flap of the crab during spwning. The diameter of the newly spawned eggs ranges was 366 + 38 um. It is significantly increased to 497 + 3 um after 253 hrs 55 mins just prior to hatching. Formation of the eye was observed after about 120 hrs 14 mins. The heartbeat/min increased significantly from 22 (143 hrs 46 mins) to 219 beats/min seconds away from hatching (253 hrs 55 mins). There were about 1.5 x 10 6 first zoeae (Z1) individuals that hatched from a 295 g berried female after 10 days of incubation at 28.77 + 0.79 C and 30 ppt ; while the 575 g broodstock hatched about 8.5 x 10 5 zoea-one (Z1) larvae after 12 days at 27.29 + 0.50 C and 27.42 + 2.79 ppt. The newly hatched larvae were cultured at six different salinity levels (15, 20, 25, 30, 33-34 control, 35 and 40 ppt) at 27.01 + 1.08 0C for 20 days. Water was changed daily. Brachionusplicatilis (25 ind/ml) and Artemiasalinanauplii(8 ind/ml) were given as larval food every morning. Highest survival (31.67%) was attained in the control at 33-34 ppt but this is not significantly )P>0.01) different to 13.33 % at 30 and 35 ppt. The larvae were able to tolerate salinity of 20 and 40 ppt with 5.0 and 1.67% survival, respectively, and not significantly (P>0.01) different to 0 % survival obtained at 15 ppt. Larval survival at 25 ppt was 10%. This shows that the larvae can tolerate salinity of 25-35 ppt and can metamorphose to megalopa with a 10-31.67% survival rate for 20 days. Highest mean mortality of the treatments was observed from zoea-one (Z1) tozoea-two (Z2). Larval mortalities decreased toward the later stages of development, Besides osmotic and ionic stress, cannibalism and inefficiency to catch food at the earlier stage could be the cause of the mortality. Further study s needed to exactly pinpoint the cause of mortality. Based from larval survival on molting and metamorphosis, the ideal salinity for molting to zoea-two and zoea-three is at 33-34 ppt, zoea-four at 40 ppt salinity, zoea-five at 33-34 ppt or 20 pptsalinity ; and metamorphosis to megalopa at 30 or 40 ppt salinity. These suggest that a fluctuating salinity from 30-35 ppt can be used for all larval stages.